Apakah Struktur Aktiva dan Ukuran Perusahaan Berpengaruh terhadap Struktur Modal Perusahaan Makanan dan Minuman? - Tarmizi Taher; Caria Ningsih; Oman Sukirman (JURNAL BISNIS HOSPITALITI, 2021)
Capital is important for the Firm both as a driver of the Firm's operations and as a reflection of the Firm's financial condition. Therefore, it is necessary to plan a good capital structure to maximize the use of capital. This research aims to analyze the influence of the Firm size and the asset structure on the capital structure of the food and beverage subsector companies listed on the Indonesia Stock Exchange for the period 2013-2019.The population of this study is all food and beverage subsector companies listed on the Indonesia Stock Exchange; samples are selected using purposive sampling methods based on certain criteria. The data in this study is secondary data from the Firm's financial statements for the period 2013-2019. Data processing uses classic assumption tests and multiple linear regression analysis using the Eviews 9 application. The results showed that the Firm size partially negatively and insignificantly affects the capital structure while the asset structure partially positively and significantly affects the capital structure. The Firm size and the asset structure simultaneously have a significant effect on the capital structure.